Predicting Value of ALCAM as a Target Gene of microRNA-483-5p in Patients with Early Recurrence in Hepatocellular Carcinoma - Lu, Xin-Yuan; Chen, Di; Gu, Xiao-Yuan; Ding, Jie; Zhao, Ying-Jun; Zhao, Qian; Yao, Ming; Chen, Zhiao; He, Xiang-Huo; Cong, Wen-Ming (Frontiers in Pharmacology, 2018)
Postoperative recurrenthepatocellular carcinoma (RHCC)seriously affectsthe clinical prognosis of patients. Many studies have indicated that microRNAs play an important role in HCC, but there has been no research of clonal origins on RHCC by analzing microRNAs. In the present study, we found that miR-483-5p was significantly upregulated in RHCC tissues of short-term recurrence(≤ 2 years) by miRNA microarray screening, and can significantly promote migration and invasion of HCC cells in vitro and increase intrahepatic metastasis in nude mice in vivo. Furthermore, we demonstrated that activated leukocyte cell adhesion molecule (ALCAM), which significantly suppressed migration and invasion of HCC cells, was a direct target of miR-483-5p, and the re-introduction of ALCAM expression could antagonise the promoting effects of miR-483-5p on the capacity of HCC cells for migration and invasion. In addition, expression level of ALCAM was negatively correlated with microvascular invasion and tumor size, which were recognized prognostic factors. The cases which were negative for ALCAM expression had shorter time to recurrence than positive cases, and univariate and multivariate survival analyses showed that ALCAM was an independent risk factor of HCC recurrence. qRT-PCR and Western blotting showed that the expression of EMT related genes (MMP-2, MMP-9, E-caherin and vimentin) significantly changed as a result of interfering or overexpression of ALCAM, and ALCAM was significantly associated with EMT in HCC. These results suggest that the miR-483-5p / ALCAM axis is an important regulator in invasion and metastasis and biomarker for recurrence risk assessment of HCC.